Threshold and recovery of anaerobic digestion under high ammonia stress: influence of COD/NH4+ ratio and CO2 enrichment - Javad Bardi, Mohammad; Müller, Felix; Polag, Daniela; Habtu, Nigus G.; Koch, Konrad (Bioresource technology, 2025)
This study underscores the importance of maintaining an optimal chemical oxygen demand to ammonia (COD/NH4+) ratio to ensure stable anaerobic digestion (AD) performance. The optimal COD/NH4+ ratio ranges from 24.0 to 33.0, while a critical threshold is identified between 11.0 and 17.0, below which AD performance declines. However, the AD of protein-rich substrates typically operates under an “inhibited steady-state” condition, characterized by a lower COD/NH4+ level. At lower COD/NH4+ ratios, the acetoclastic methanogenesis is inhibited, while hydrogenotrophic methanogens remain active, as evidenced by an increase of over 96 mUr in δ2H-CH4 isotope values. The CO2 enrichment of AD under lower COD/NH4+ ratios demonstrate to be a promising approach for AD recovery and performance stabilization. The CO2 enrichment showed a rapid full recovery in methane production at a COD/NH4+ ratio as low as 7.0 (6.2 gNH4+-N/L) and a slower but still effective recovery up to a COD/NH4+ ratio of 5.0 (10 gNH4+-N/L). The δ2H-CH4 isotope values from CO2-enriched ADs indicated a well-balanced methanogenic community, in contrast to non-enriched ADs, which exhibited clearly lower acetoclastic activity. Therefore, CO2 enrichment is promising for enhancing AD recovery and stability at high ammonia stress, promoting methanogenic balance and boosting methane production.